STUDENTS’ AUTONOMOUS LEARNING IN VOCABULARY ACQUISITION OF 7TH GRADE AT SMPN 35 SURABAYA - Attaroqiya, Nailal Himmah; Imaniar, Fahmy; Oktaviani, Ita Eka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vocabulary acquisition is a crucial aspect of English language learning, especially for seventh-grade students at SMPN 35 Surabaya. This study aims to examine the level of learning autonomy demonstrated by seventh-grade students in acquiring English vocabulary and to identify the autonomous vocabulary-learning strategies. The study used a mixed method with a descriptive quantitative-qualitative approach. Data were collected through a questionnaire consisting of Likert-scale and open-ended questions, completed by 52 seventh-grade students at SMPN 35 Surabaya. The data were analyzed descriptively to describe the level of autonomy based on the aspects of initiation, monitoring, and evaluation, as well as the comprehension acquisition strategies applied by students. The result showed that most students had a high level of autonomy, as evidenced by their ability to initiate learning, master comprehension, and assess learning outcome. Frequently used strategies included the use of learning applications, audiovisual media, social interaction, and individual techniques such as note-taking and memorization. These findings confirm that strengthening all three aspects of autonomy is crucial to support more effective and sustainable comprehension acquisition.